MORPHOLOGY OF BIOMPHALARIA GLABRATA HEMOCYTES AND THEIR INTERACTION WITH MIRACIDIUM OF SHISTOSOMA MANSONI - ‎A. Farahnak; H. Ghobadi F. Bagheri (Acta Medica Iranica, 2005)
Schistosomiasis is the second most common parasitic cause of death, after malaria. Biomphalaria glabrata is a fresh water snail with medical importance since it is the intermediate host of Schistosoma mansoni, an agent of schistosomiasis. The internal defense system of B. glabrata snails is mostly represented by circulating elements of the hemolymph, hemocytes, which are important factors in fighting against infections in snails. The purpose of this study was morphological study of B. glabrata hemocytes and their interaction with miracidia of Schistosoma mansoni. B. glabrata hemolymph was collected by heart puncture and a differential count of hemocytes was done in dyed preparations. Dyeing with Giemsa revealed two cell types: type 1, hemocytes with basophilic nucleus, little cytoplasm and sub-spherical shape and type 2, nucleated hemocytes, uniformly basophilic and spherical shape. Hemocytes showed cytoadherence and encapsulation after 1 h of miracidium-hemocyte incubation. These results could be of concern in the control programs of schistosomiasis.